Analisis Hukum Islam terhadap Anak yang Tidak Melaksanakan Wasiat Orang Tua - Ahmad Sholeh; Muhammad Yusron Maulana El-Yunusi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the provisions of Islamic law regarding the implementation of wills and to examine the legal consequences for heirs who fail to carry out their parents’ wills. This research employs a normative legal method with juridical, conceptual, and maqāṣid al-syarī‘ah approaches. The data sources consist of primary legal materials, including the Qur’an, Hadith, and the Compilation of Islamic Law (KHI), as well as secondary materials such as scholarly journals and relevant literature. Data were collected through library research and analyzed using a descriptive-analytical method. The findings indicate that wills in Islamic law have a strong normative foundation and are limited to a maximum of one-third of the estate, and they are not intended for heirs unless approved by all heirs. Non-compliance by heirs is influenced by economic factors, lack of legal understanding, and internal family conflicts. From the perspective of Islamic law, such non-compliance contradicts the principles of trustworthiness and justice and does not align with the objectives of Islamic law in preserving wealth and maintaining family harmony. Juridically, a valid will has binding legal force and can serve as a basis for dispute resolution in the Religious Courts; therefore, enhancing public legal awareness is essential to ensure its proper implementation.